A Pluri-Ethno-Linguistic Fragmentation Index - Cassilde, Stephanie; Labart, Kelly (Revista Internacional de Organizaciones, 2020)
The Ethno-Linguistic Fragmentation index aims to measure the probability two random individuals belong to the same groupe. However, a person may belong to several groups. The Pluri-Ethno-Linguistic Fragmentation index generalizes the ELF index to consider multiple belongings within a country. PELF index results are discussed from the crucial case of Luxemburg. PELF index is computed in work, friends, and family linguistic environments; PELF is significantly smaller than ELF. The difference between ELF and PELF index for Luxemburg suggests a high linguistic cohesion at work and with friends.